Vancouver's Island, the Hudson's Bay Company, and the government [electronic resource] - Fitzgerald, James Edward, 1818-1896. (London : Simmonds, 1848)
'(Reprinted from the "Colonial Magazine" for September, 1848).' Electronic reproduction. Mode of access: Internet. 44